Review: Persistent pioneers; Borassus L. and Corypha L. in Malesia - GRAHAM E. EAGLETON (Biodiversitas Journal of Biological Diversity, 2016)
Eagleton G.E. 2016. Review: Persistent Pioneers; Borassus L. and Corypha L. in Malesia. Biodiversitas 17: 716-732. This review traces advances in taxonomic and ethnobotanic understanding of the genera Corypha L. and Borassus L. gained from research since the time of publication of â€œHarvest of the Palm; Ecological Change in Eastern Indonesiaâ€™â€™ by James J. Fox in 1977. It posits testable hypotheses arising from the literature: firstly, that both genera were present in the furthest parts of island Southeast Asia prior to a definitive Indianized cultural expansion in the first millennium CE.; secondly, that two of their species Ì¶ â€œlontarâ€ Borassus flabellifer L. and â€œgewangâ€ Corypha utan Lam. Ì¶ were significant components of pre-agricultural economies of the archipelago, but that their full economic exploitation benefited from later cultural stimuli from the Indian subcontinent. To test these hypotheses, lines of research with potential benefits for local economies in semi-arid Indonesia are proposed.